The impact of human insecurity on human development in Iraq - Assi. Lect: Hayder Jawad Kadhum (Journal of College of Education, 2025)
The study addresses the concept of human development, its characteristics and features, such as productivity, fairness, equality, empowerment, and sustainability, and how these features are closely linked to human security. It indicates that any decline in development levels affects, in one way or another, the human security of the individual or group. The research demonstrated that human development seeks to achieve the security of individuals living within the state to meet the needs of current and future generations, as well as to strive to achieve sustainable human development. It highlighted the most significant problems of insecurity, including inadequate health and educational levels, poverty, destitution, and unemployment, all of which contribute to a decline in development levels. The researcher adopts the descriptive approach in his study to reach the desired results. The study highlights the importance of achieving sustainable human development and warned about the risks associated with losing human security and its effects on society. The research reached several conclusions and recommendations, including: Human security is of extreme importance in achieving stability and well-being for society. For human development to be sustainable and effectively meet the needs of current and future generations, it must be characterized by fairness, equality, continuity, empowerment, and productivity. It is necessary for relevant authorities to develop the necessary plans and programs to provide human security, as it is necessary to activate legislation that requires the individuals to enjoy a high level of education, health, and income to achieve personal security and development for the individual.
Keywords: human security, sustainable development, human development, unemployment, poverty, community well-being